INTENSIFICATION OF STUDENTS’ COGNITIVE ACTIVITY WHILE FORMING SKILLS OF ENGLISH MONOLOGUE SPEECH (EXPERIENCE EXCHANGE) - Holubnycha, Lyudmyla Оleksandrivna (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2018)
Introduction. Search of the ways to intensify students’ cognitive activity is very important for modern system of higher education. Training foreign languages in particular English in higher educational non-linguistic institutions is, on the one hand, very vital in global society, on the other, complicated in the situation of shortage of academic hours. As the main purpose of learning foreign language is to de able to speak this language the major aim of the teachers is to form monologue speech skills. So they are looking for the means to do it and intensification of students’ cognitive activity facilitates it as well. Purpose. It is to exchange the experience of ways of increasing students’ cognitive activity while forming skills of monologue speech at English classes in non-linguistic higher educational institutions. Results. The problem of students’ cognitive activity intensification is researched on the basis of forming skills of English monologue statement which is associated with professional oriented oral topics which are common for teaching students of non-language higher educational institutions. The main characteristics of monologue speech such as contextual conditionality, one-pointedness, preparedness, continuity, consistency, completeness and coherence of presentation of thoughts are presented. The analysis of the features of monologue speech, which is based on professional oriented oral topics and so is vital for non-linguistic higher educational institutions, is fulfilled. It is made with the consideration of possibilities to intensify students’ cognitive activity. These features include: relatively low level of problematic content of conversational topics; descriptive character of statements; availability of printed text which represents the topic. Originality. On the bases of work with students of Law University at English lessons the experience of enhancing students’ cognitive activity aimed teaching monologue skills associated with training oral topic is shown. So, well-known method of three stages of training monologue speech is presented through personally worked out system of exercises for students of Law University. Conclusion. Intensification of students’ cognitive activity is to become the foundation for forming skills of monologue statement. Applying communicative assessments is one of the best ways to increase students’ cognitive activity. Creative teacher may always improve existing methods of training get the results. The subsequent research of the problem of students’ cognitive activity intensification having purpose to forming skills of foreign language monologue statement may be connected with using innovative technologies, partnership and others.